PERANAN E-LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH MENENGAH PERTAMA (SMP) - Fitriani; Nurjannah (Universitas Sulawesi Barat, 2019)
Mathematics lessons are one of the subjects that must be studied by students in every level of education, especially in the field of junior high school (SMP). If you look at the mathematics learning objectives in Permendikbud Number 21 Year 2016 requires students to have the ability to think logically, analytically, systematically, critically and creatively. But mathematical material is abstract, making mathematics considered difficult by most students. This is one of the causes for not achieving the goals of mathematics learning. Mathematical concepts can be easily understood if they are concrete and follow the times experienced by students. The stage of development of junior high school students requires students to be able to reason by using abstract and symbolic things. One solution is to help students understand mathematical material using e-learning. Learning e-learning is a concept of education that utilizes the development of information and communication technology, especially in the teaching and learning process. The ease of learning with e-learning is also the teacher can prepare learning effectively and efficiently by using media and learning resources that are more interesting so that they are not focused on printed books. This can increase students' interest in learning where learning is no longer focused on the teacher and class. The function of e-learning in supporting learning activities in the classroom is as a supplement (additional), complement (complementary) and substitution (substitute). Based on the description of the explanation above, it can be concluded that the purpose of writing this paper is to describe how the role of e-learning in learning junior high school (SMP) mathematics.